Theory of the contemporary historical novel: typological models and methodological synthesis - Bokiev, Nurali Abdurashid ugli (The Lingua Spectrum, 2026)
This study examines the theoretical foundations of the historical novel and its development in American literature in the second half of the twentieth century. It draws on the key concepts of E. Fleishman, G. Hörner, H. White, L. Hutcheon, A. Nünning, and J. De Groot to outline the major stages in the evolution of the genre. Particular attention is devoted to the postmodern concept of historiographic metafiction, including its theoretical significance, narrative functions, and literary manifestations. The study argues that the boundary between historical and fictional narratives is fluid, interconnected, and shaped by cultural and interpretive frameworks, emphasizing the constructed nature of historical knowledge. Nünning’s typology is applied to distinguish different types of historical novels according to their treatment of historical material and narrative strategies. In addition, narratological analysis explores the role of the narrator, temporal organization, and narrative reliability in shaping the “effect of history.” Methodologically, the research adopts a synthetic approach, integrating multiple perspectives and offering a comprehensive interpretation of the historical novel.